2022
DOI: 10.1186/s12904-021-00894-0
|View full text |Cite
|
Sign up to set email alerts
|

Preference for initiation of end-of-life care discussion in Indonesia: a quantitative study

Abstract: Background Initiating discussion about death and dying is often considered a difficult topic for healthcare providers, thus there is a need for further research to understand this area, particularly in developing countries. The aim of this study was to describe preferences for the initiation of end-of-life care discussions in Indonesia, comparing the general population and health care professionals. Methods This cross-sectional, descriptive study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In 70% of these patients, the illness is at an advanced stage [ 8 ], where advance care planning may have added value. Although a survey among participants from a general population in Indonesia showed that the majority wished to be informed about a possible life threatening disease and be engaged in end-of-life communication, a study on the perspectives of Indonesian patients has not been performed [ 9 ]. However, the stigma surrounding cancer prevented people to have an open communication about it [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 70% of these patients, the illness is at an advanced stage [ 8 ], where advance care planning may have added value. Although a survey among participants from a general population in Indonesia showed that the majority wished to be informed about a possible life threatening disease and be engaged in end-of-life communication, a study on the perspectives of Indonesian patients has not been performed [ 9 ]. However, the stigma surrounding cancer prevented people to have an open communication about it [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Understand-ing the cultural practice of death and dying in palliative care service therefore is essential to enable providing quality palliative care and end-of-life care. However, available studies particularly in Asian countries have focused on death and prognosis discussion (Eng et al, 2022;Huang et al, 2018;Sudhakar et al, 2020) and rituals associated with such events (Cheng et al, 2015).…”
Section: Introductionmentioning
confidence: 99%